Species Delimitation and Evolutionary History of Tree Frogs in the Hyla chinensis Group (Hylidae, Amphibian) - Yan, Peng; Pan, Tao; Wu, Guiyou; Kang, Xing; Ali, Izaz; Zhou, Wenliang; Li, Jiatang; Wu, Xiaobing; Zhang, Baowei (Frontiers in Ecology and Evolution, 2020)
Species are the cornerstone in many domains of biology research, which make the accurate species delimitation became critically important. In this study, the systematics and biogeography of the Hyla chinensis-group were analyzed based on phylogeny, species delimitation and ancestral area reconstruction methods. The phylogenetic results showed six specific clusters existed in the H. chinensis-group. BPP analysis indicated that six distinct species exist due to the high probability values (>0.95), which were also supported by the BF analysis. The divergence time of the H. chinensis-group was estimated to date back to 18.84 Mya in the early Miocene. Combining the results of ancestral area reconstruction, the H. chinensis-group might have originated from Guangxi-Hainan, then spread eastwardly and reached Nanling mountains, Wuyi mountains, Huangshan mountains and Taiwan. In rightabout colonization, it was gradually extended to the Yunnan-Guizhou Plateau, Sichuan basin, Qinling mountains and Dabie mountains. Considering the geological movement from early Miocene to Pliocene, the colonization pattern of the H. chinensis-group maybe closely related to the progressive uplift of Qinghai-Tibetan Plateau (QTP) and historical climate change. Our study provided evidence for species delimitation and speciation process within the H. chinensis-group. Our study supported the hypothesis that the evolutionary divergence in this species group was a consequence of the progressive uplift of QTP and environmental change.